2020
DOI: 10.1039/d0sc04461j
|View full text |Cite
|
Sign up to set email alerts
|

Regioisomeric control of layered crystallinity in solution-processable organic semiconductors

Abstract: Construction and control of 2D layered molecular packing motifs with functionally substituted π-electron cores are crucial for developing organic electronic materials and devices. We investigated a regioisomeric structure–property relationship in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 83 publications
(93 reference statements)
0
32
0
Order By: Relevance
“…In OSCs, alkyl chain substitutions of π-cores are often used to increase the solvent solubility, which is an indispensable function for their application in printed electronics technology. It was recently demonstrated that one-sided unsymmetric substitutions of π-cores with long alkyl chains enable the formation of a unique bilayer-type LHB (b-LHB) packing, which considerably enhances the layered crystallinity. These effects have been revealed with several compounds, such as [1]­benzothieno­[3,2- b ]­[1]­benzothiophene (BTBT), benzothieno­[3,2- b ]­naphtho­[2,3- b ]­thiophene (BTNT), ,, and benzo­[1,2- b :4,5- b ]­bis­[ b ]­benzothiophene (BBBT) derivatives. The adjacent intermolecular interactions between the alkyl chains stabilize the layered molecular packing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In OSCs, alkyl chain substitutions of π-cores are often used to increase the solvent solubility, which is an indispensable function for their application in printed electronics technology. It was recently demonstrated that one-sided unsymmetric substitutions of π-cores with long alkyl chains enable the formation of a unique bilayer-type LHB (b-LHB) packing, which considerably enhances the layered crystallinity. These effects have been revealed with several compounds, such as [1]­benzothieno­[3,2- b ]­[1]­benzothiophene (BTBT), benzothieno­[3,2- b ]­naphtho­[2,3- b ]­thiophene (BTNT), ,, and benzo­[1,2- b :4,5- b ]­bis­[ b ]­benzothiophene (BBBT) derivatives. The adjacent intermolecular interactions between the alkyl chains stabilize the layered molecular packing.…”
Section: Introductionmentioning
confidence: 99%
“…The flexible nature of the alkyl chains probably contributes to enhancing the layered crystallinity by complementing the 2D ordering of rigid π-cores. The substituted alkyl chains usually form all-trans conformations in the layered crystals and their stretching direction from the π-core is variable, which enables the formation of alkyl chain layers that are adaptable to the alignment of the π-core layers. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Alkyl substituents also affect other critical characteristics of organic semiconductors such as solution processability and molecular packing motif (e.g., brickwork vs herringbone). These alkyl group effects are generally subtle and hard to predict; therefore, molecular design of organic semiconductors often involves experimental screening of structures and positions of alkyl substituents. , …”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that the layered crystallinity is enhanced by elaborate end-cap substitutions of some extended π-cores. One-sided alkyl chain substitution allowed the formation of a bilayer-type layered herringbone ( b -LHB) packing, which clearly enhanced the layered crystallinity. , In the b -LHB packing, unidirectionally oriented monomolecular layers were formed, in which the alkyl chains played essential roles in architecting the layered molecular assembly. Furthermore, the other-sided end-capping with a phenyl group may have assisted in the formation of the b -LHB packing, , probably by suppressing the long-axis molecular slip.…”
Section: Introductionmentioning
confidence: 99%